An X-ray absorption spectroscopy investigation of the coordination environment of electrogenerated Ni(ii)-pseudohalide complexes arising from the anodic polarization of Ni electrodes in DMSO solutions of NCO−, NCS− and NCSe− ions1. Issue 20 (6th March 2015) - Alwis, Kethsiri H. K. L.; Ingham, Bridget; Mucalo, Michael R.; Kappen, Peter; Glover, Chris
<x xml:space="preserve">Abstract</x> EXAFS/XANES measurements combined with IR spectroelectrochemistry directly probe in situ the coordination sphere of electrogenerated ions in metal electrode systems so obviating the need to isolate ions unchanged from the electrolyte for analysis.